Relationship of Family Support with Anxiety Level on Preoperative Patients - Titik Juwariyah; Eko Dian Hadi S; Nurhidayah Nurhidayah (Jurnal Pendidikan dan Konseling (JPDK), 2020)
Preoperative preparation is very important to minimize the risks of surgery because the final results of a surgery really depend on the assessment of the patient's condition before surgery. Anxiety in pre-op patients can increase the patient's psychological stimulus, in this case it greatly influences the patient's emotions, so that it can increase blood pressure and even make the patient afraid and uncooperative during surgery. In this case, family support is really needed by preoperative patients to reduce anxiety. This study aims to determine the relationship between family support and anxiety levels in pre-operative patients in the inpatient room at Undaan Eye Hospital, Surabaya. The research design used was analytical survey research using a cross sectional approach. The population in this study was the total number of pre-operative patients in the Inpatient Room at the Undaan Eye Hospital, Surabaya, namely 20 respondents in March 2021 with. The number of samples in this study was 19 respondents. The independent variable is pre-operative patient anxiety. Dependent variable is Family Support. Data collection was carried out using a questionnaire. Data was expressed on an ordinal scale and analyzed using the Spearman rank statistical test. The research results showed that 18 respondents received high family support (95%), only 1 respondent received moderate support (5%). It was found that 13 respondents did not experience anxiety (68%), and only 1 respondent experienced severe anxiety (5%). Using the Spearman rank statistical test, it was obtained (p) = 0.010, which means that H0 was rejected or there was a relationship between family support and the preoperative anxiety level of patients at the Undaan Eye Hospital, Surabaya. The conclusion of this research is that there is a relationship between family support and the level of anxiety in pre-operative patients in the inpatient ward of the Mata Undaan Hospital, Surabaya. As long as the respondent is in a stressful period due to undergoing surgery, if at that time they receive family support, the psychological burden they experience will be reduced